Implementasi Kebijakan Pelayanan Pajak Bumi dan Bangunan (PBB) Pada Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Hastika Rahayu Hs; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2022)
Policy implementation is a way for a policy to achieve its goals. Implementation is a general process of administrative action that can be investigated at a certain program level, this study aims to determine the implementation of the Land and Building Tax (PBB) service policy at the Medan City Regional Tax and Retribution Management Agency and to find out and analyze the factors that influence it. The form of this research belongs to descriptive research that uses qualitative data analysis, namely this research is investigated by observation or observation, interviews, and describes the state of the object of research based on the facts. There were 11 informants in this study. Data collection techniques were obtained from interviews, observations, and documentation. While the data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the implementation of the Land and Building Tax (PBB) service policy at the Regional Tax and Retribution Management Agency of Medan City has not gone well. This can be seen from the lack of good communication, resources and bureaucratic structure. Factors that influence not going well are lack of knowledge, perception, physical condition, gender and community living environment, lack of human resources in charge of Land and Building Tax (PBB) services, lack of a special budget allocated for equipment Land and Building Tax (PBB) services, obstacles often occur so that the Service Operational Standards (SOP) are sometimes not met.